Conceptual groundwater modelling in an alluvial aquifer of upper Narmada basin - NEMA, S.; AWASTHI, M. K.; NEMA, R. K. (Journal of Soil and Water Conservation, 2020)
Ground water decline is a serious concern all over the world led by excessive ground water exploitation. The efficient monitoring and forecast of ground water is quite essential for sustainability of livelihood and future planning. The current study demonstrate the development of conceptual model in an alluvial aquifer which can be used to solve practical ground water problem as well as to make predictions for future. This study was conducted in Tawa command area, which lies in Hoshangabad, District of Madhya Pradesh, India, having the problem of water logging and water scarce condition in few specific region. The 2-Layer conceptual ground water model was developed considering hydrological, hydrogeological and topographical framework for the study area. The developed model fits very well to the observations with optimized values of recharge, specific yields and hydraulic conductivities. The ground water predictions have been made by the validated conceptual model for the future. Study also suggested the efficient strategically planning of study area for the future.